2017
DOI: 10.1371/journal.pone.0169669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varroa destructor, Wounding and Varroa Homogenate on Gene Expression in Brood and Adult Honey Bees

Abstract: Honey bee (Apis mellifera) gene expression related to immunity for hymenoptaecin (AmHym) and defensin-1 (AmDef-1), longevity for vitellogenin (AmVit2) and stem cell proliferation for poly U binding factor 68 kDa (AmPuf68) was compared following Varroa destructor parasitism, buffer injection and injection of V. destructor compounds in its homogenate. In adults, V. destructor parasitism decreased expression of all four genes, while buffer injection decreased expression of AmHym, AmPuf68 and AmVit2, and homogenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 46 publications
0
30
1
1
Order By: Relevance
“…There is considerable debate on the nature of the Varroa-Apis interaction and whether the mites possess the ability to suppress the host's immune response (Gregory et al, 2005, Kuster et al, 2014, Khongphinitbunjong et al, 2015, Koleoglu et al, 2017. Through label free analysis of the parasitized worker and drone pupae, the proteins significantly altered in abundance were examined for the presence of immune factors.…”
Section: Proteins Involved In the Immune Responsementioning
confidence: 99%
“…There is considerable debate on the nature of the Varroa-Apis interaction and whether the mites possess the ability to suppress the host's immune response (Gregory et al, 2005, Kuster et al, 2014, Khongphinitbunjong et al, 2015, Koleoglu et al, 2017. Through label free analysis of the parasitized worker and drone pupae, the proteins significantly altered in abundance were examined for the presence of immune factors.…”
Section: Proteins Involved In the Immune Responsementioning
confidence: 99%
“…destructor parasitism is a very serious health problem for honey bees as the mite not only damages the bee by feeding on the hemolymph and fat tissue [7,8], but it also vectors a number of viruses with deformed wing virus (DWV) being the most pathogenic to honey bees [9,10]. Additionally, V. destructor impairs the humoral and cellular responses of the immune system of honey bees [11,12,13]. Furthermore, V. destructor has been reported to affect the neural processes of honey bees by impairing grooming behaviour [14], non-associative learning [15] and homing ability in worker bees [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a correlation between this obligate parasite and viral load of the deformed wing virus (DWV), the Israeli acute paralysis virus (IAPV), and other less well-known viruses (Chen et al 2004;Di Prisco et al 2011a, b;Yang and Cox-Foster 2007). Additionally, varroa causes direct physical damage/deformities from feeding (Kanbar and Engels 2003), compromises host immune systems (Koleoglu et al 2017), and increases host mortality (Guzman-Novoa et al 2010). As a harmful pest of agriculturally important honey bees, varroa poses a tremendous threat to the bee-keeping industry (Gibbs and Muirhead 1998;Ellis et al 2010), and thus food security.…”
Section: Introductionmentioning
confidence: 99%